Türkiye and Russia Relations Within the Framework of Turkiye's Energy Policy - HAMZAÇEBİ, RÜMEYSA (İstanbul Kültür Üniversitesi, 2022)
The main factor that provides economic, social, political and many areas of development of countries is to use of energy. Energy resources are the most vital inputs of daily life and production is made for energy and industrial products. For this reason, those who govern the country and undertake managerial roles in energy have to supply energy through uninterrupted, reliable, timely, clean and cheap ways to meet the needs of society and the energy sector. Given the energy supply security, they must also provide energy at the most affordable prices and diversify these sources. In this regard, the energy policy put forward by the states should be self-renewing, consistent and realistic, and should also be target-oriented. This study focuses on how Türkiye became a role model in energy policy and this policy's repercussions on the bilateral relations between Türkiye and Russia. The main purpose of this thesis is to answer whether the relations between Türkiye and Russia are based on energy competition or strategic partnerships.
Türkiye'nin Enerji Politikası Kapsamında Türkiye ve Rusya İlişkisi
▪ Yüksek lisans tezi.